Level of Knowledge about Covid 19 during Pregnancy. - Dr. Jannatul Ferdous; Dr. Mohammad Mostafizur Rahman; Dr. Fakhria Alam (SSB Global Journal of Medical Science, 2024)
Introduction: Coronavirus disease (COVID-19) is a respiratory disease. The aim of this study was to assess the level and knowledge and types of attitudes towards COVID-19 among pregnant women attending OPD of Gynecology for an antenatal check-up in Chattogram Medical College Hospital of Bangladesh. Methods: This was an interview-based cross-sectional study that was conducted at the Department of Obstetric Gynae, Ashiyan Medical College Hospital, Barua Khilkhet, Dhaka, Bangladesh during the period from 1st June to 30th July 2020. In total 100 pregnant women who had an antenatal check-up for their current pregnancy in the hospital during the study period were selected as the study population. All data were processed, analyzed, and deiminated by MS Office and SPSS version 25 as per need. Result: The majority of the participants were young adults aged between 25-34 years old. Most of them (79%) were housewives. 64% of theparticipants were of middle economic status. The majority of theparticipants believed fever and dry cough to be a symptom of COVID-19.73% believed that pregnant women have a higher risk with COVID-19 than others. 38% thought that COVID is common only in a coldclimate, but 49% disagreed with this fact. Proper knowledge of COVID-19 was common in 41% of the participants only. And 35% of the totalparticipants had a positive attitude towards the current pandemic, whichwas below satisfaction level. Conclusion: knowledge level of the participants was found satisfactory but the attitude was found lower than the general satisfaction level.